Effect of premedication on side effect frequency in patients to whom immunotherapy is applied (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate whether there are differences in terms of the frequency and severity of side effects in patients to whom premedication were given/or not before the application of subcutaneous allergen specific immunotherapy.Material and method: Patients receiving subcutaneous allergen-specific immunotherapy in our clinic between October 2014 and October 2015 were evaluated for side effects. In patients to whom subcutaneous allergen-specific immunotherapy was applied and reaction was occurred against this therapy; allergen type, reaction intensity and duration, and also use of premedication were recorded. When the patients were assessed in terms of side effects; edema and/or erythema from 2 to 5 cm, which were beginning within the first 24 hours in the injection site. That was defined as ‘local reaction’ and edema and/or erythema, if it was greater than 5 cm defined as ‘broad local reaction’.Results: Total of 101 patients, to whom allergen specific immunotherapy was applied, were included. In a year of the study; total of 660 injections were applied to 101 patients and reaction to injections were observed in 31 injections (4.6%). Reaction was observed in 20 individuals (19.8%). No significant difference was found between premedicated and non-premedicated groups in terms of the percentage of side effects and risk of side effects (p >0.59). Conclusion: In our study; patients with or without premedication were compared in terms of side effect frequency. In premedication group; ratio of local reaction was found to be low (20%). It was thought that premedication could reduce local reactions but did not prevent extensive local reaction. There was no difference when comparing the side effect frequency between the two groups. Keywords: Premedication; Immunotherapy; Side Effect.
Keywords: Premedication; Immunotherapy; Side Effect.